2019
DOI: 10.1186/s12888-019-2130-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential cost-effectiveness of a vocational rehabilitation program for individuals with schizophrenia in a high-income welfare society

Abstract: Background Over the past decades research has shown that employment has a positive impact on quality of life, global functioning and recovery in individuals with schizophrenia. However, access to vocational rehabilitation services for this group is limited and unemployment rates remain high. In this study we explore the potential cost-effectiveness of a novel vocational rehabilitation program (The Job Management Program – JUMP) earmarked for individuals with schizophrenia in Norway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
13
1
1
Order By: Relevance
“…This study revealed that individuals with schizophrenia are able to start small businesses, work in a formal setting and even learn new skills that will help them live and sustain a productive life. This is consistent with the finding that individuals with schizophrenia in paid jobs have boosted morale and increased quality of life 30 . Although the participants in this study earn less than a dollar per day, they stated that the amount is sufficient to meet their basic needs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study revealed that individuals with schizophrenia are able to start small businesses, work in a formal setting and even learn new skills that will help them live and sustain a productive life. This is consistent with the finding that individuals with schizophrenia in paid jobs have boosted morale and increased quality of life 30 . Although the participants in this study earn less than a dollar per day, they stated that the amount is sufficient to meet their basic needs.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the finding that individuals with schizophrenia in paid jobs have boosted morale and increased quality of life. 30 Although the participants in this study earn less than a dollar per day, they stated that the amount is sufficient to meet their basic needs.…”
Section: Discussionmentioning
confidence: 82%
“…The augmented VR program JUMP has previously documented cost-effectiveness, improved occupational outcomes and improved levels of apathy and neurocognition [14,16,42]. In this study, causal pathways were assessed, by means of g-estimation, to quantify the magnitude and nature of specific effects that were targets in the CBT and CR groups.…”
Section: Discussionmentioning
confidence: 99%
“…The JUMP Study was a randomized, multisite hybrid VR program for adults with psychotic disorder in Norway [ 12 14 ]. Significant improvements in occupational outcomes were found in both groups (VR + CR versus VR + CBT) across an observation period of two years, with a non-significant group difference [ 15 17 ]. Also, both neurocognition and symptoms improved, so far best documented with respect to neurocognitive measures [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a place-support approach. Job placement was first thought could have negative effects in the patient group with a high-stress sensitivity, but studies have later shown that instead of creating a burden for patients, having a job reduced hospitalizations, increased quality of life, and decreased cost with high rates of entering and staying in a job ( 66 68 ). Supported employment is recommended by treatment guidelines ( 26 – 28 , 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%